COLLABORATIVE PROFICIENCY TESTING IN FORENSIC SCIENCE LABORATORIES - A. Sidorova (Теория и практика судебной экспертизы)
The author describes the experience of conducting inter-laboratory testing with theparticipation of the Computer Forensics Laboratory of the Russian Federal Center ofForensic Science.